PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBANTUAN SOFTWARE CONSTRUCT 2 PADA MATERI JURNAL PENYESUAIAN PERUSAHAAN DAGANG - Rochmah, Afifatur; Bahtiar, Moh Danang (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
The increasingly advanced era of education requires teachers to be able to use the right technology to improve the quality of learning, motivate students, and create a pleasant learning atmosphere. One way is to develop interactive learning media with the help of construct 2 software. The purpose of this development research is to produce interactive learning media products based on applications and websites on the material of trade company adjustment journals that are feasible to use and test their effectiveness on learning outcomes. This type of research is development research with the ADDIE development model. The subjects of this study were material experts, media experts, linguists and students of class XI Accounting at SMK Negeri 4 Surabaya. Questionnaires and tests were used as research instruments. The feasibility results of the material expert validation were obtained at 91%, media experts at 91%, linguists at 98% and the field trial resulted in a student response of 98%. In testing the effectiveness, it can be seen that there are differences in learning outcomes between the control class without the use of media and the experimental class with the use of media. From these results it can be concluded that interactive learning media is feasible and effective to use in the learning process.